Policy Implementation of Sustainable Tourism Development Program in Manado City - Fahri Juarsa Muhammad; R. Ira Irawati; Mas Halimah (Institute of Computer Science (IOCS), 2021)
Sustainable tourism development requires stakeholder participation to ensure broad participation. Systematic policies in tourism development are needed, especially in realizing sustainable tourism development in the city of Manado. With the regulation of the Minister of Tourism Number 14 of 2016 concerning Guidelines for Sustainable Tourism Destinations which is supported by Regional Regulation Number 2 of 2020 concerning RIPPARDA, the purpose of this research is to explore the extent to which policies are implemented in the context of sustainable tourism development in Manado City. This study uses qualitative methods through a phenomenological approach with qualitative observations, qualitative interviews and qualitative documents. The results of current research, tourism in Manado City continues to be developed starting from tourist destination infrastructure, MSME locations are also revitalized by related parties, HR training both external and internal, coordination continues to be built with stakeholders in organizing tourism events, as well as participation from the community in provide criticism or input on the tourism development of Manado City, which is still at the consultation stage with the Manado City Tourism Office, as well as a decrease in Manado City's PAD which is dominated by the tourism sector due to the current COVID-19 pandemic.